2023
DOI: 10.1021/jacsau.2c00630
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Assembly of Ferrocenes with Axial and Planar Chiralities via Palladium/Chiral Norbornene Cooperative Catalysis

Abstract: The preparation of ferrocenes with both axial and planar chiralities poses a considerable challenge. Herein, we report a strategy for the construction of both axial and planar chiralities in a ferrocene system via palladium/chiral norbornene (Pd/NBE*) cooperative catalysis. In this domino reaction, the first established axial chirality is dictated by Pd/NBE* cooperative catalysis, while the latter planar chirality is controlled by the preinstalled axial chirality through a unique axial-to-planar diastereoinduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…It was found that the two ortho substituents of 2 had a significant influence on the reaction regarding both reactivity and stereoselectivity. Generally, one ortho electron-withdrawing group was required to secure both good reactivity and excellent enantioselectivity, such as ester ( 22 and 32 ), amide ( 33 , 34, and 41 ), nitro ( 36 ), phosphoryl ,, ( 42 ), and free carboxylic acid ( 35 ), while the other ortho -substituent of 2 could be extended to alkyl ( 22 and 26 ), hydroxymethyl ( 31 ), TBS-protected hydroxymethyl ( 30 ), chloro ( 27 ), and naphthyl ( 40–42 ) groups, providing the corresponding products with excellent enantioselectivities (95–99% e.e). No enantioselectivity was observed when the sterically less hindered ortho fluoro group was introduced, which is mainly due to the low configurational stability of the product ( 28 ), as supported by the DFT-calculated rotational barrier (Δ G rot ‡ = 27.7 kcal/mol, Figure , vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the two ortho substituents of 2 had a significant influence on the reaction regarding both reactivity and stereoselectivity. Generally, one ortho electron-withdrawing group was required to secure both good reactivity and excellent enantioselectivity, such as ester ( 22 and 32 ), amide ( 33 , 34, and 41 ), nitro ( 36 ), phosphoryl ,, ( 42 ), and free carboxylic acid ( 35 ), while the other ortho -substituent of 2 could be extended to alkyl ( 22 and 26 ), hydroxymethyl ( 31 ), TBS-protected hydroxymethyl ( 30 ), chloro ( 27 ), and naphthyl ( 40–42 ) groups, providing the corresponding products with excellent enantioselectivities (95–99% e.e). No enantioselectivity was observed when the sterically less hindered ortho fluoro group was introduced, which is mainly due to the low configurational stability of the product ( 28 ), as supported by the DFT-calculated rotational barrier (Δ G rot ‡ = 27.7 kcal/mol, Figure , vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Dong independently developed a Pd 0 /NBE*-promoted resolution of racemic epoxides through annulation with aryl iodides (Figure E, ii) . As a step toward our goal of developing versatile Pd 0 /NBE* cooperative catalysis, we have also realized the construction of axial chiral biaryls, C–N axial chirality, 1,2-diaxial o -terphenyls, and kinetic resolution of tertiary benzyl alcohols successively since 2020 . This full account comprehensively delineates our efforts in developing the atroposelective ortho -C–H arylation of aryl iodides through Pd 0 /NBE* cooperative catalysis that ultimately leads to a general and modular platform for the construction of C–C axial chirality, C–N axial chirality, and chiral fluorenols, including the reaction design, detailed reaction condition optimization, more extensive substrate scope explorations, and axially configurational stability studies.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, without an external terminating reagent, this chemistry can be extended to the synthesis of dihydrobenzofurans (DHBFs) under slightly modified conditions from Scheme (Scheme A) . Notably, N 1 is still the optimal cocatalyst for this reaction, and only 10 mol % is required, which, to the best of our knowledge, represents the lowest NBE cocatalyst loading in Catellani-type reactions. , It is worth mentioning that this method can be applied in the two-step synthesis of a 5-HT 2C receptor agonist family with 8-aryl-substituted DHBF as the common core structure (>200 members) (Scheme B) . Subjecting 2-aryl-substituted phenyl iodides 1e – g and commercially available chiral epoxide 2e to the standard reaction conditions, the desired chiral 2,3-dihydrobenzofuran products 13e – g were obtained in moderate to good yields.…”
Section: Development Of New Annulations Based On Pd/nbe Cooperative C...mentioning
confidence: 99%
“…In recent years, Pd/norbornene (NBE)-based cooperatively catalyzed Catellani-type reaction has become a valuable multicomponent strategy for the synthesis of polysubstituted arenes. [102] Using this strategy, Liang's group [103] (Scheme 53a) and Zhou's group [104] (Scheme 53b) independently realized the synthesis of ferrocene derivatives bearing axial and planar chirality. Under Pd/NBE cooperative catalysis, ortho-ferrocene-tethered aryl iodides 228 or 231 and aryl bromides 229 or 232 underwent a Catellani reaction, followed by selective CÀ H functionalization to obtain ferrocenes 230 or 233 bearing axial and planar chirality with excellent enantio-and diastereoselectivities.…”
Section: Atropisomers With Other Chiral Elementsmentioning
confidence: 99%